Estrategias educativas que contribuyan a disminuir la incidencia del abandono del esquema de vacunación en niños menores de dos años de la comunidad de Ilumán, provincia de Imbabura - Irua Jaramillo, Carmen Geovanna (2018)
The present research had as objective to develop educational strategies that contribute to avoid the desertion by the parents of family in the application of the vaccination scheme of the children under two years of the Community of llumán, province of Imbabura; at present, the Vaccination Scheme, has the vaccines against the six main diseases considered high lethality for children, which are applied free of charge as a guarantee of the state as a right of the population and a duty of the population to maintain its financing; for the development of the present research the qualitative and quantitative paradigms, methods, techniques and research instruments were used, which helped to identify the causes of the lack of compliance of the vaccination scheme in children under two years, being the line of research health management and disease prevention; is a basic scheme but broadly represents the participants in the strategy and, based on this, it was determined that the proposal will contribute to socialize and empower the same users of the communities, and specifically in the health center of llumán, canton Otavalo, province Imbabura